Chinese exports and US import prices - Benjamin R. Mandel (Federal Reserve Bank of New York, 2013)
This paper develops a technique to decompose price distributions into contributions from markups and marginal cost. The estimators are then used as a laboratory to measure the relationship between increasing Chinese competition and the components of U.S. import prices. The estimates suggest that the intensifi cation of Chinese exports in the 2000s corresponded to substantial changes in the distributions of both the markups and marginal cost of U.S. imports. The entry of a Chinese exporter in an industry corresponded to rest-of-world exporters shrinking their markup (lowering prices by up to 30 percent) and increasing their marginal cost (raising prices by up to 50 percent). The fact that marginal cost increased as competition stiffened strongly suggests that the composition of non-Chinese exports shifted toward higher-quality varieties. The estimates also imply a pattern in the acquisition of market share by Chinese exporters: They enter at relatively low cost/quality and then subsequently undertake quality improvements and markup reductions. These results provide some of the fi rst measures of the dual nature of trade's procompetitive effects; exporters respond to tougher competition by simultaneously adjusting both markups and quality.
Keywords: F10; F14; L10; 330; Procompetitive effects of trade; markup measurement